2021
DOI: 10.3390/cancers13143641
|View full text |Cite
|
Sign up to set email alerts
|

A Nationwide Study on the Impact of Routine Testing for EGFR Mutations in Advanced NSCLC Reveals Distinct Survival Patterns Based on EGFR Mutation Subclasses

Abstract: EGFR mutation analysis in non-small-cell lung cancer (NSCLC) patients is currently standard-of-care. We determined the uptake of EGFR testing, test results and survival of EGFR-mutant NSCLC patients in the Netherlands, with the overall objective to characterize the landscape of clinically actionable EGFR mutations and determine the role and clinical relevance of uncommon and composite EGFR mutations. Non-squamous NSCLC patients diagnosed in 2013, 2015 and 2017 were identified in the Netherlands Cancer Registry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 81 publications
4
16
0
Order By: Relevance
“…Molecular diagnostics have become standard in clinical routine to identify patients who may benefit from targeted therapy or immunotherapy 7. However, previous Dutch studies showed that the molecular testing rate increased significantly from 73% in 2013 to 81% in 2017 41 42. Though, about 15% of the patients did not receive targeted therapy despite presence of a targetable mutation 43.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular diagnostics have become standard in clinical routine to identify patients who may benefit from targeted therapy or immunotherapy 7. However, previous Dutch studies showed that the molecular testing rate increased significantly from 73% in 2013 to 81% in 2017 41 42. Though, about 15% of the patients did not receive targeted therapy despite presence of a targetable mutation 43.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, not starting TKI might be associated with molecular testing. Testing for EGFR mutations has been standard-of-care in the Netherlands since 2011, but next generation sequencing for EGFR has gradually been implemented into the routine setting for nonsquamous NSCLC [18]. Although, the Netherlands is a small western country with easy access to care, especially in the early years of study patients might have chosen for other first-line treatments due to limited availability of EGFR testing or treatment near their home.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the association of EGFR mutations with favorable prognostic factors might act as a confounding factor in these types of analysis. Furthermore, given the large spectrum of EGFR mutations in LUAD, it remains to be seen whether prognosis is affected differently by distinct mutations or mutation subgroups [ 30 ]. TP53 status was also informative: thus, in line with previous observations [ 31 ], our study found that TP53 mutations had negative prognostic value in early-stage LUAD patients.…”
Section: Discussionmentioning
confidence: 99%